Sex-associated differences in incentive salience and drinking behaviour in a rodent model of alcohol relapse - Hakus, Aileen; Foo, Jerome Clifford; Casquero-Veiga, Marta; Gül, Asude Zülal; Hintz, Franziska; Rivalan, Marion; Winter, York; Priller, Josef; Hadar, Ravit; Winter, Christine (Addiction biology, 2025)
The ability of environmental cues to trigger alcohol-seeking behaviours is thought to facilitate problematic alcohol use. Individuals' tendency to attribute incentive salience to cues may increase the risk of addiction. We sought to study the relationship between incentive salience and alcohol addiction using non-preferring rats to model the heterogeneity of human alcohol consumption, investigating both males and females. Adult rats were subjected to the alcohol deprivation effect (ADE) paradigm, where they were given voluntary access to different alcohol solutions with repeated interruptions by deprivation and reintroduction phases over a protracted period (five Alcohol Deprivation Cycles). Before each Alcohol Deprivation Cycle, rats were tested in the Pavlovian Conditioned Approach (PCA) paradigm, which quantifies the individual salience toward a conditional cue and the reward, thus allowing us to trace the process of attributing incentive salience to reward cues. During the final Alcohol Deprivation Cycle (ADE5), animals were tested for compulsive-like behaviour using quinine taste adulteration. We investigated sex differences in drinking behaviour and PCA performance. We observed thatb females drank significantly more alcohol than males and displayed more sign-tracking (ST) behaviour in the PCA, whereas males showed goal-tracking (GT) behaviour. Furthermore, we found that high drinkers exhibited more ST behaviour. The initial PCA phenotype was correlated with later alcohol consumption. Our findings indicate a complex relationship between incentive salience and alcohol addiction and emphasize the importance of considering both sexes in preclinical research.